Power cable protection tube and method of manufacturing the same

CN122992556APending Publication Date: 2026-10-27SHANGHAI SHANGSU HLDG GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611310098.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]针对现有技术的不足,本发明提供一种电力电缆保护管及其制备方法,通过内导热扩散层、外导热散热层和间隔设置的径向导热桥构成“切向扩散-径向传递-外部扩散”的立体导热网络,并利用承载层维持保护管的机械性能,从而解决现有片状导热填料在挤出过程中沿管体轴向和管壁切平面取向,导致管材轴向导热性能提高而径向散热能力不足,以及高填料用量造成管材韧性下降的问题

Benefits of technology

[0049]与现有技术相比,本发明提供了一种电力电缆保护管及其制备方法,具备以下有益效果:通过内导热扩散层中的片状六方氮化硼沿管壁切平面排列,能够将电缆与保护管局部接触位置或邻近位置产生的集中热量沿周向和轴向扩散,使热量到达多个径向导热桥,减小局部热斑。径向导热桥贯穿承载层并与内、外导热层熔融连接,球形氧化铝和球形氮化硼团聚颗粒在径向导热桥内构成低取向敏感性的导热网络,能够将内导热扩散层的热量跨越低导热承载层传递至外导热散热层。外导热散热层进一步将径向导热桥输出的热量沿保护管外表面扩散,增大保护管与周围回填材料之间的有效换热面积。高填料含量主要设置在厚度较小的内、外导热层及间隔设置的径向导热桥内,承载层保持连续聚合物相,避免整个管壁高填料化造成环刚度、韧性和落锤冲击性能明显下降。径向导热桥两端的T形或燕尾形锚固段能够提高界面熔接面积,并通过几何互锁限制热循环过程中的层间剥离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992556A_ABST
    Figure CN122992556A_ABST
Patent Text Reader

Abstract

The application discloses a power cable protection pipe and a preparation method thereof, and relates to the technical field of power cable laying protection and heat-conducting polymer composite pipe materials, and comprises an inner heat-conducting diffusion layer, a bearing layer and an outer heat-conducting and radiating layer which are sequentially arranged from inside to outside along the radial direction. A plurality of radial heat-conducting bridges are arranged in the bearing layer. The radial heat-conducting bridges continuously extend along the axial direction of the pipe body and are spacedly distributed along the circumferential direction of the pipe body. The radial heat-conducting bridges penetrate through the bearing layer along the thickness direction of the pipe wall, the inner ends of the radial heat-conducting bridges are melt-connected with the inner heat-conducting diffusion layer, and the outer ends of the radial heat-conducting bridges are melt-connected with the outer heat-conducting and radiating layer. The sheet-shaped hexagonal boron nitride in the inner heat-conducting diffusion layer is arranged along the tangent plane of the pipe wall, so that the concentrated heat generated at the local contact position or the adjacent position of the cable and the protection pipe can be diffused along the circumferential direction and the axial direction, the heat can reach the plurality of radial heat-conducting bridges, and the local hot spot is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable laying protection and thermally conductive polymer composite pipe technology, specifically to a power cable protection pipe and its preparation method. Background Technology

[0002] Power cable protection pipes are typically buried in roads, green belts, substations, cable ducts, or trenchless construction areas to isolate power cables from soil, moisture, corrosive media, and external mechanical loads, and to provide access for cable installation, maintenance, and replacement. Existing protection pipes are mostly made of modified polypropylene, high-density polyethylene, or other thermoplastic resins, offering advantages such as corrosion resistance, electrical insulation, and ease of continuous extrusion molding.

[0003] During cable operation, the heat generated by the conductor and insulation layer needs to diffuse sequentially through the cable outer sheath, the air gap between the cable and the protective pipe, the pipe wall, and the backfill material outside the pipe to the surrounding soil. Polypropylene and high-density polyethylene have low intrinsic thermal conductivity, and the cable and the protective pipe usually cannot maintain complete surface contact. Therefore, the protective pipe and its internal air layer can easily become thermal resistance links in the radial heat dissipation path of the cable.

[0004] Existing technologies typically improve the thermal conductivity of protective tubes by adding hexagonal boron nitride, alumina, aluminum nitride, or other insulating and thermally conductive fillers to the polyolefin matrix. However, when protective tubes are manufactured using continuous extrusion methods, the sheet-like thermally conductive fillers tend to align along the melt flow direction and the tangential plane of the tube wall under melt shearing and stretching. The resulting thermally conductive network is mainly distributed along the axial and circumferential directions of the tube body. Since cable heat needs to be transferred from the inside to the outside of the tube along the tube wall thickness direction, an increase in the thermal conductivity measured in ordinary samples does not necessarily mean a simultaneous increase in the radial thermal conductivity of the protective tube.

[0005] If a significantly increased amount of sheet-like thermally conductive filler is used to form a filler contact network spanning the pipe wall thickness, it will increase melt viscosity and extrusion pressure, increasing the risk of filler agglomeration, surface defects, and poor interlayer bonding, and weakening the pipe's toughness, drop hammer impact resistance, and interfacial stability under long-term thermal cycling conditions. Uniformly adding a high proportion of thermally conductive filler throughout the entire pipe wall may also disrupt the continuous polymer phase of the load-bearing layer, making it difficult for the protective pipe to simultaneously maintain ring stiffness and impact resistance.

[0006] Therefore, the specific technical problem to be solved is: how to utilize the tangential orientation formed during the extrusion process of sheet-like insulating thermally conductive filler to achieve heat diffusion on the inner and outer surfaces of the tube wall, while establishing a continuous insulating thermally conductive path that runs through the thickness of the tube wall in the bearing layer, thereby improving the radial thermal conductivity of the protective tube without relying on the high filler content of the entire tube wall, while taking into account ring stiffness, impact resistance, electrical insulation performance and interface stability after thermal cycling. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides a power cable protection pipe and its manufacturing method. The pipe forms a three-dimensional heat-conducting network of "tangential diffusion-radial transmission-external diffusion" through an inner heat-conducting diffusion layer, an outer heat-conducting heat dissipation layer, and spaced radial heat-conducting bridges. The mechanical properties of the protection pipe are maintained by a load-bearing layer. This solves the problems of existing sheet-like heat-conducting fillers being oriented along the pipe axis and the tangential plane of the pipe wall during extrusion, resulting in improved axial heat conduction but insufficient radial heat dissipation capacity, and high filler content causing a decrease in pipe toughness.

[0008] In this specification, "radial" refers to the direction from the axis of the protective tube to the outer side of the tube wall; "axial" refers to the direction parallel to the central axis of the protective tube; and "circumferential" refers to the circumferential direction around the central axis of the protective tube.

[0009] The "pipe wall tangent plane" refers to the plane that is tangent to the corresponding coaxial cylindrical surface at any radial position of the protective pipe.

[0010] "Radial thermal bridge" refers to a region of thermally conductive material that extends continuously along the axial direction of the protective tube, is distributed circumferentially, and connects the inner thermal diffusion layer and the outer thermal dissipation layer along the tube wall thickness direction.

[0011] The "radial heat bridge cross-sectional area ratio" is calculated based on the cross-section perpendicular to the axis of the protective tube. It is the ratio of the area occupied by all radial heat bridges within the bearing layer to the cross-sectional area of ​​the bearing layer.

[0012] "Orientation ratio of sheet-like insulating and thermally conductive filler" refers to the percentage of particles with an angle of no more than 30° between the surface of the particle and the tangential plane of the pipe wall at the location of the randomly selected no less than 300 sheet-like filler particles.

[0013] "Aspect ratio" refers to the ratio of the maximum Freret diameter to the minimum Freret diameter of a particle; the aspect ratio of granular insulating and thermally conductive fillers is no greater than 3, while the aspect ratio of sheet-like insulating and thermally conductive fillers is 10 to 80.

[0014] To achieve the above objectives, the present invention provides the following technical solution: a power cable protection pipe, comprising an inner heat-conducting diffusion layer, a bearing layer, and an outer heat-conducting heat dissipation layer arranged radially from the inside to the outside.

[0015] Multiple radial heat-conducting bridges are arranged within the bearing layer. Each radial heat-conducting bridge extends continuously along the axial direction of the tube body and is spaced apart along the circumference of the tube body; the radial heat-conducting bridge penetrates the bearing layer along the thickness direction of the tube wall, and its inner end is fused to the inner heat-conducting diffusion layer, and its outer end is fused to the outer heat-conducting heat dissipation layer.

[0016] The inner thermal diffusion layer and the outer thermal dissipation layer each consist of a polyolefin matrix and a sheet-like insulating thermally conductive filler, respectively. The sheet-like insulating thermally conductive filler is arranged mainly along the tangential plane of the pipe wall at its location, so that the heat entering the inner thermal diffusion layer diffuses along the circumference and axial direction of the pipe body to multiple radial thermal bridges, and the heat output from the radial thermal bridges diffuses within the outer thermal dissipation layer.

[0017] Radial thermal bridges consist of a polyolefin matrix and granular insulating thermally conductive fillers with an aspect ratio not greater than 3. Granular insulating thermally conductive fillers are less likely to form the same degree of unidirectional orientation as sheet-like fillers, thus creating a thermally conductive connection path across the thickness of the load-bearing layer within the radial thermal bridge.

[0018] Preferably, the number of radial heat-conducting bridges is 8 to 24, and they are evenly distributed along the circumference of the tube body; the circumferential width of each radial heat-conducting bridge is 2 to 8 mm, and the area occupied by all radial heat-conducting bridges in the cross section perpendicular to the tube body axis is 5% to 18% of the cross-sectional area of ​​the bearing layer.

[0019] When the radial thermal bridge cross-sectional area accounts for less than 5%, the number of thermal bridges distributed circumferentially along the pipe wall or the effective heat transfer area is insufficient, and the heat collected in the inner thermal diffusion layer cannot pass through the bearing layer in time; when the proportion is higher than 18%, the continuous resin area of ​​the bearing layer is excessively divided, and the stiffness of the protective pipe ring and the drop hammer impact performance decrease.

[0020] Preferably, the radial thermal bridge includes a bridging section and anchoring sections located at the inner and outer ends of the bridging section, respectively. The circumferential width of the anchoring section is 1.2 to 2.5 times the circumferential width of the bridging section. The inner anchoring section is embedded with an inner thermally diffusing layer, and the outer anchoring section is embedded with an outer thermally dissipating layer, thereby forming a T-shaped or dovetail-shaped weld interface.

[0021] The anchoring section can increase the fusion area between the radial thermal bridge and the adjacent thermal conductive layer, and limit the radial thermal bridge from radial shrinkage, circumferential separation or interface warping relative to the load-bearing layer and thermal conductive layer during thermal cycling.

[0022] Preferably, the inner thermally conductive diffusion layer, the load-bearing layer, the outer thermally conductive heat dissipation layer, and the radial thermally conductive bridge are made of the same type of base resin. The base resin is polypropylene, high-density polyethylene, or a blend of polypropylene and high-density polyethylene.

[0023] The inner thermal diffusion layer, the outer thermal heat dissipation layer, and the radial thermal bridge each contain 2 to 8 parts by weight of maleic anhydride-grafted polyolefin relative to 100 parts by weight of the main resin, in order to improve the dispersibility of inorganic thermally conductive fillers in the polyolefin matrix and improve the interfacial compatibility between different melts.

[0024] Preferably, the sheet-like insulating and thermally conductive filler is hexagonal boron nitride, with an average particle size D50 of 5-30 μm and an aspect ratio of 10-80; the amount of hexagonal boron nitride used relative to 100 parts by weight of polyolefin matrix is ​​8-25 parts by weight.

[0025] In the inner heat-conducting diffusion layer and the outer heat-conducting heat dissipation layer, at least 60% of the hexagonal boron nitride flakes have an angle of no more than 30° between them and the tangential plane of the tube wall at their location.

[0026] Preferably, the granular insulating and thermally conductive filler includes spherical alumina and spherical boron nitride agglomerates, with a mass ratio of spherical alumina to spherical boron nitride agglomerates of 2:1 to 8:1, and a total amount of 25 to 55 parts by weight per 100 parts by weight of polyolefin matrix.

[0027] Spherical alumina exhibits high structural stability and filling efficiency, while spherical boron nitride agglomerates reduce interfacial thermal resistance between different inorganic particles. The two types of particles fill the gaps between each other through particle size gradation, increasing the number of effective contact points within the radial thermal bridge while maintaining the same total filler content.

[0028] Preferably, the support layer comprises the following raw materials in parts by weight: The composition includes 75-88 parts of impact copolymer polypropylene, 6-15 parts of polyolefin elastomer, 5-12 parts of talc, 1-5 parts of maleic anhydride grafted polypropylene, and 0.2-0.8 parts of antioxidant.

[0029] Preferably, the thickness of the inner heat-conducting diffusion layer is 0.3 to 1.2 mm, the thickness of the outer heat-conducting heat dissipation layer is 0.5 to 1.5 mm, and the thickness of the bearing layer accounts for 60% to 85% of the total wall thickness of the protective tube.

[0030] This invention also provides a method for preparing a power cable protection pipe, comprising the following steps: S1, Raw material pretreatment The flake-shaped hexagonal boron nitride, spherical alumina, and spherical boron nitride agglomerates were dried at 100–120 °C for 2–4 h.

[0031] Prepare an ethanol-water solution by adding 0.3% to 1.5% of the silane coupling agent by mass of the corresponding thermally conductive filler. Spray the solution onto the surface of the flake-shaped hexagonal boron nitride and the granular insulating thermally conductive filler, respectively. Mix for 20 to 40 minutes, and then dry at 90 to 110°C for 1 to 3 hours.

[0032] The preferred silane coupling agent is γ-glycidoxypropyltrimethoxysilane.

[0033] S2, preparation of internal and external thermally conductive masterbatch The polyolefin base resin, maleic anhydride grafted polyolefin, and antioxidant are added through the main feed port of the twin-screw extruder, while the surface-treated flake hexagonal boron nitride is added through the side feed port located in the rear half of the screw.

[0034] The temperature in each zone of the twin-screw extruder is 165–210℃, and the screw speed is 150–350 r / min. The melt is extruded, cooled, and pelletized to obtain thermally conductive masterbatch.

[0035] Thermally conductive masterbatch and polyolefin main resin are diluted in a set ratio to prepare inner thermally conductive material and outer thermally conductive material, respectively.

[0036] Adding flaky hexagonal boron nitride from the rear side feed port can reduce the breakage of flaky particles in the high-shear mixing zone, thus maintaining the specified length-to-diameter ratio.

[0037] S3, Radial Thermal Bridge Masterbatch Preparation Spherical alumina, spherical boron nitride agglomerates, maleic anhydride-grafted polyolefins, and part of the main resin are premixed, and then extruded, cooled, and pelletized by twin-screw extrusion to obtain radial thermal bridge masterbatch.

[0038] The radial thermal bridge masterbatch is mixed with the remaining main resin to make the total amount of particulate insulating thermally conductive filler reach 25 to 55 parts by weight per 100 parts by weight of polyolefin matrix, thus obtaining the thermal bridge material.

[0039] S4. Preparation of load-bearing layer material Impact copolymer polypropylene, polyolefin elastomer, talc, maleic anhydride grafted polypropylene and antioxidant are mixed and then melt-blended and granulated using a twin-screw extruder to obtain the load-bearing layer material.

[0040] S5, multi-channel co-extrusion molding The inner thermally conductive material, the supporting layer material, the outer thermally conductive material, and the thermal bridge material are fed into four extruders respectively to form the inner thermally conductive melt, the supporting layer melt, the outer thermally conductive melt, and the thermal bridge melt.

[0041] The co-extrusion die includes an inner annular flow channel, a middle annular flow channel, an outer annular flow channel, and multiple radial slit flow channels spaced apart along the circumference.

[0042] The inner heat-conducting melt enters the inner annular flow channel, the supporting layer melt enters the middle annular flow channel, and the outer heat-conducting melt enters the outer annular flow channel. The heat-conducting bridge melt enters the radial slit flow channel, and the outlet of the radial slit flow channel passes through the middle annular flow channel radially and connects with the inner and outer annular flow channels respectively.

[0043] Widening cavities are provided at both ends of the radial slit channel, thereby forming T-shaped or dovetail-shaped anchoring sections at the inner and outer ends of the radial heat-conducting bridge, respectively.

[0044] The ratio of the length of the directional section to the corresponding channel gap in the inner and outer annular flow channels is 20–60. The pressure of the thermally conductive bridge melt entering the radial slit flow channel is 1.05–1.25 times the pressure of the load-bearing layer melt, and the co-extrusion temperature is 175–215℃.

[0045] The shear flow in the inner and outer annular channels causes the flakes of the hexagonal boron nitride to align along the tangential plane of the tube wall; the radial slit channel causes the granular insulating and thermally conductive filler to form a continuous radial thermally conductive region.

[0046] S6, sizing, heat treatment and cooling The tube blank formed by co-extrusion enters the vacuum sizing box and undergoes preliminary sizing and cooling under the conditions of negative pressure of 0.02 to 0.06 MPa and cooling water temperature of 15 to 35°C.

[0047] After sizing, the pipes are heat-treated at 80–120℃ for 15–45 min, then cooled to room temperature at an average cooling rate of 3–10℃ / min, and subsequently pulled, cut and end-faced.

[0048] Heat treatment is used to reduce residual stress caused by different shrinkage rates between regions with different filler contents, and to improve the interface stability between the radial thermal bridge and the inner and outer thermal conductive layers.

[0049] Compared with existing technologies, this invention provides a power cable protection pipe and its preparation method, which has the following beneficial effects: By arranging plate-like hexagonal boron nitride along the tangential plane of the pipe wall in the inner heat-conducting diffusion layer, concentrated heat generated at or near the local contact point between the cable and the protection pipe can be diffused circumferentially and axially, allowing heat to reach multiple radial heat-conducting bridges and reducing localized hot spots. The radial heat-conducting bridges penetrate the load-bearing layer and are fused together with the inner and outer heat-conducting layers. Spherical alumina and spherical boron nitride agglomerates form a low-orientation-sensitivity heat-conducting network within the radial heat-conducting bridges, enabling the heat from the inner heat-conducting diffusion layer to be transferred across the low-thermal-conductivity load-bearing layer to the outer heat-conducting heat dissipation layer. The outer heat-conducting heat dissipation layer further diffuses the heat output from the radial heat-conducting bridges along the outer surface of the protection pipe, increasing the effective heat exchange area between the protection pipe and the surrounding backfill material. The high filler content is mainly set in the thinner inner and outer heat-conducting layers and the spaced radial heat-conducting bridges, while the load-bearing layer maintains a continuous polymer phase, avoiding a significant decrease in ring stiffness, toughness, and drop-weight impact performance caused by high filler content throughout the pipe wall. The T-shaped or dovetail-shaped anchoring sections at both ends of the radial thermal bridge can increase the interfacial welding area and limit interlayer delamination during thermal cycling through geometric interlocking.

[0050] The inner thermal diffusion layer, the load-bearing layer, the outer thermal heat dissipation layer, and the radial thermal bridge are made of the same or compatible polyolefin main resin. The compatibility between filler-resin and different melts is improved by grafting polyolefin with maleic anhydride, so that the protective tube can maintain stable thermal conductivity and mechanical properties after long-term thermal aging and cold and hot cycles. Attached Figure Description

[0051] Figure 1 This is a backscattered electron scanning electron microscope image of the radial cross-section of the power cable protection pipe in Example 2; Figure 2 This is a scanning electron microscope image of the sheet-like hexagonal boron nitride orientation structure in the thermally conductive diffusion layer of Example 2. Detailed Implementation

[0052] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0053] Please see Figure 1 and Figure 2 This invention provides a technical solution for a power cable protection pipe and its preparation method: Unless otherwise stated, all parts used in the examples are by weight.

[0054] The melt flow rate of the impact copolymer polypropylene is 0.5–1.5 g / 10 min, and the test conditions are 230 °C and 2.16 kg.

[0055] The melt flow rate of high-density polyethylene is 0.2–0.8 g / 10 min, and the test conditions are 190 °C and 5 kg.

[0056] The polyolefin elastomer is an ethylene-octene copolymer.

[0057] The grafting rates of maleic anhydride-grafted polypropylene and maleic anhydride-grafted polyethylene are 0.8% to 1.2%.

[0058] Different particle sizes and aspect ratios of the plate-shaped hexagonal boron nitride were selected according to the examples.

[0059] The average particle size D50 of the spherical alumina is 10-30 μm, and the aspect ratio is no greater than 1.5.

[0060] The average particle size D50 of the spherical boron nitride agglomerates is 20–60 μm, and the aspect ratio is no greater than 3.

[0061] The antioxidant is composed of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1:1.

[0062] All embodiments use protective tubes with a nominal outer diameter of 110 mm. Unless otherwise specified, the radial thermal bridge adopts a T-shaped anchoring structure.

[0063] Example 1 The inner heat-conducting diffusion layer and the outer heat-conducting heat dissipation layer are made of 100 parts of impact-resistant copolymer polypropylene, 2 parts of maleic anhydride-grafted polypropylene, 8 parts of flake hexagonal boron nitride, and 0.3 parts of antioxidant.

[0064] The average particle size D50 of the plate-like hexagonal boron nitride is 5 μm, and the aspect ratio is 10.

[0065] The radial thermal bridge is composed of 100 parts impact-resistant copolymer polypropylene, 2 parts maleic anhydride-grafted polypropylene, 16.7 parts spherical alumina, 8.3 parts spherical boron nitride agglomerates, and 0.3 parts antioxidant. The total amount of granular insulating thermally conductive filler is 25 parts, and the mass ratio of spherical alumina to spherical boron nitride agglomerates is 2:1.

[0066] The load-bearing layer consists of 75 parts impact-resistant copolymer polypropylene, 6 parts polyolefin elastomer, 5 parts talc, 1 part maleic anhydride-grafted polypropylene, and 0.2 parts antioxidant.

[0067] There are 8 radial heat-conducting bridges, the circumferential width of the bridging section is 2mm, the cross-sectional area of ​​the radial heat-conducting bridge accounts for 5% of the cross-sectional area of ​​the bearing layer, and the width of the anchoring section is 1.2 times the width of the bridging section.

[0068] The inner thermal diffusion layer has a thickness of 0.3 mm, the outer thermal heat dissipation layer has a thickness of 0.5 mm, and the load-bearing layer accounts for 85% of the total wall thickness.

[0069] The silane coupling agent used for filler surface treatment is 0.3% of the filler mass.

[0070] The ratio of the length of the inner and outer annular flow channel directional section to the flow channel gap is 20, the melt pressure of the thermal bridge is 1.05 times the melt pressure of the bearing layer, and the co-extrusion temperature is 175℃.

[0071] The tube blank was sized under a negative pressure of 0.02 MPa and a cooling water temperature of 15℃, then heat-treated at 80℃ for 15 min and cooled to room temperature at a rate of 3℃ / min.

[0072] The measured proportions of hexagonal boron nitride orientation in the inner and outer thermal conductive layers were 62.1% and 61.7%, respectively.

[0073] Example 2 The inner thermal diffusion layer and the outer thermal heat dissipation layer are made of 100 parts of impact-resistant copolymer polypropylene, 5 parts of maleic anhydride-grafted polypropylene, 16.5 parts of flake hexagonal boron nitride, and 0.5 parts of antioxidant.

[0074] The average particle size D50 of the plate-like hexagonal boron nitride is 17.5 μm, and the aspect ratio is 45.

[0075] The radial thermal bridge is composed of 100 parts impact-resistant copolymer polypropylene, 5 parts maleic anhydride-grafted polypropylene, 33.3 parts spherical alumina, 6.7 parts spherical boron nitride agglomerates, and 0.5 parts antioxidant. The total amount of granular insulating thermally conductive filler is 40 parts, with a mass ratio of 5:1.

[0076] The load-bearing layer is composed of 81.5 parts impact copolymer polypropylene, 10.5 parts polyolefin elastomer, 8.5 parts talc, 3 parts maleic anhydride grafted polypropylene, and 0.5 parts antioxidant.

[0077] There are 16 radial heat-conducting bridges, the circumferential width of the bridging section is 5mm, the cross-sectional area of ​​the radial heat-conducting bridge accounts for 11.5%, and the width of the anchoring section is 1.85 times the width of the bridging section.

[0078] The inner thermal diffusion layer has a thickness of 0.75 mm, the outer thermal heat dissipation layer has a thickness of 1.0 mm, and the load-bearing layer accounts for 72.5% of the total wall thickness.

[0079] The amount of silane coupling agent used is 0.9% of the filler mass.

[0080] The ratio of the length of the inner and outer annular flow channel directional section to the flow channel gap is 40, the melt pressure of the thermal bridge is 1.15 times the melt pressure of the bearing layer, and the co-extrusion temperature is 195℃.

[0081] The tube blank was sized under a negative pressure of 0.04 MPa and a cooling water temperature of 25°C, then heat-treated at 100°C for 30 min and cooled to room temperature at a rate of 6.5°C / min.

[0082] The measured proportions of hexagonal boron nitride orientation in the inner and outer thermal conductive layers were 75.8% and 74.9%, respectively.

[0083] Example 3 The inner heat-conducting diffusion layer and the outer heat-conducting heat dissipation layer are made of 100 parts of impact-resistant copolymer polypropylene, 8 parts of maleic anhydride-grafted polypropylene, 25 parts of flake hexagonal boron nitride, and 0.8 parts of antioxidant.

[0084] The average particle size D50 of the plate-like hexagonal boron nitride is 30 μm, and the aspect ratio is 80.

[0085] The radial thermal bridge is composed of 100 parts impact-resistant copolymer polypropylene, 8 parts maleic anhydride-grafted polypropylene, 48.9 parts spherical alumina, 6.1 parts spherical boron nitride agglomerates, and 0.8 parts antioxidant. The total amount of granular insulating thermally conductive filler is 55 parts, with a mass ratio of 8:1.

[0086] The load-bearing layer consists of 88 parts impact-resistant copolymer polypropylene, 15 parts polyolefin elastomer, 12 parts talc, 5 parts maleic anhydride-grafted polypropylene, and 0.8 parts antioxidant.

[0087] There are 24 radial heat-conducting bridges, the circumferential width of the bridging section is 8mm, the cross-sectional area of ​​the radial heat-conducting bridge accounts for 18%, and the width of the anchoring section is 2.5 times the width of the bridging section.

[0088] The inner thermal diffusion layer is 1.2 mm thick, the outer thermal heat dissipation layer is 1.5 mm thick, and the load-bearing layer accounts for 60% of the total wall thickness.

[0089] The amount of silane coupling agent used is 1.5% of the filler mass.

[0090] The ratio of the length of the inner and outer annular flow channel directional section to the flow channel gap is 60, the melt pressure of the thermal bridge is 1.25 times the melt pressure of the bearing layer, and the co-extrusion temperature is 215℃.

[0091] The tube blank was sized under a negative pressure of 0.06 MPa and a cooling water temperature of 35°C, then heat-treated at 120°C for 45 min and cooled to room temperature at a rate of 10°C / min.

[0092] The measured proportions of hexagonal boron nitride orientation in the inner and outer thermal conductive layers were 84.3% and 83.6%, respectively.

[0093] Example 4 Based on Example 2, the impact-resistant copolymer polypropylene in the inner thermal diffusion layer, the bearing layer, the outer thermal heat dissipation layer and the radial thermal bridge is replaced with high-density polyethylene, and the maleic anhydride-grafted polypropylene is replaced with the same amount of maleic anhydride-grafted polyethylene.

[0094] The co-extrusion temperature was adjusted to 180℃, and the remaining formulation, structure and process parameters were the same as in Example 2.

[0095] The proportions of hexagonal boron nitride orientation in the inner and outer thermal conductive layers are 73.7% and 73.1%, respectively.

[0096] Example 5 Based on Example 2, the main resin of each layer was adjusted to be a blend of impact copolymer polypropylene and high-density polyethylene in a mass ratio of 70:30, and the maleic anhydride grafted polyolefin was a mixture of maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene in a mass ratio of 70:30.

[0097] The co-extrusion temperature was 190°C, and the other conditions were the same as in Example 2.

[0098] The proportions of hexagonal boron nitride orientation in the inner and outer thermal conductive layers are 74.6% and 74.0%, respectively.

[0099] Example 6 The raw material formulation, layer thickness, number of radial thermal bridges, proportion of thermal bridge cross-sectional area, and preparation process of Example 6 are the same as those of Example 2.

[0100] The difference lies in the fact that the widened cavities at the inner and outer ends of the radial slit channel adopt a dovetail-shaped cross section, so that the resulting radial heat-conducting bridge has a dovetail-shaped inner end anchoring section and a dovetail-shaped outer end anchoring section.

[0101] The maximum circumferential width of the anchorage section is 1.85 times the circumferential width of the bridging section.

[0102] Unless otherwise specified, the raw material batches, pipe dimensions, layer thicknesses, extrusion equipment, extrusion temperatures, cooling conditions, and testing conditions for the following comparative examples are the same as those in Example 2.

[0103] Comparative Example 1 The thermal bridge extruder and radial slot flow channel were eliminated, and the area where the original radial thermal bridge was located was completely filled with the load-bearing layer material.

[0104] The formulations and thicknesses of the inner thermal diffusion layer, the load-bearing layer, and the outer thermal heat dissipation layer are the same as in Example 2.

[0105] Comparative Example 2 Keeping the total amount of radial thermal bridge filler unchanged at 40 parts, all spherical alumina and spherical boron nitride agglomerates were replaced with the plate-shaped hexagonal boron nitride used in Example 2.

[0106] The remaining conditions are the same as in Example 2.

[0107] Comparative Example 3 Maintain a total radial thermal bridge particle filler volume of 40 parts, and replace the spherical boron nitride agglomerates with an equal mass of spherical alumina.

[0108] The remaining conditions are the same as in Example 2.

[0109] Comparative Example 4 Maintain a total radial thermal bridge particle filler volume of 40 parts, and replace spherical alumina with an equal mass of spherical boron nitride agglomerates.

[0110] The remaining conditions are the same as in Example 2.

[0111] Comparative Example 5 Keeping the number of radial heat-conducting bridges, the width of the bridging section, and the proportion of cross-sectional area unchanged, the T-shaped anchoring sections at both ends of the radial heat-conducting bridges are changed to straight connection ends with the same width as the bridging section.

[0112] The remaining conditions are the same as in Example 2.

[0113] Comparative Example 6 The maleic anhydride-grafted polypropylene in the inner thermal diffusion layer, outer thermal dissipation layer, radial thermal bridge, and load-bearing layer was completely replaced with an equal mass of impact-resistant copolymer polypropylene.

[0114] The other components and process conditions are the same as in Example 2.

[0115] Comparative Example 7 The number of radial thermal bridges is kept at 16. By reducing the width of the bridging section, the total cross-sectional area of ​​the radial thermal bridges accounts for 3% of the cross-sectional area of ​​the load-bearing layer.

[0116] Other conditions are the same as in Example 2.

[0117] Comparative Example 8 The number of radial thermal bridges is kept at 16. By increasing the width of the bridging section, the total cross-sectional area of ​​the radial thermal bridges accounts for 22% of the cross-sectional area of ​​the load-bearing layer.

[0118] Other conditions are the same as in Example 2.

[0119] Performance testing I. Radial thermal conductivity A protective tube sample with a length of 500 mm was cut, and a cylindrical aluminum heating core that was in close contact with the inner wall was installed inside the sample, and a constant temperature water jacket was installed outside the sample.

[0120] The effective measurement section is located in the middle 300mm of the sample, with 100mm heat insulation protection sections at both ends. The external constant temperature water is maintained at 25℃, and the heating core is heated with constant power. A steady state is considered reached when the temperature fluctuations of both the inner and outer walls do not exceed 0.2℃ within 30 minutes.

[0121] After deducting the heat loss of the unloaded device, the radial thermal conductivity is calculated using the following formula:

[0122] Where λr is the radial thermal conductivity, Q is the steady-state heat transfer power of the effective measurement section, r1 is the inner radius of the protective tube, r2 is the outer radius of the protective tube, L is the length of the effective measurement section, T1 is the average temperature of the inner wall, and T2 is the average temperature of the outer wall.

[0123] Five items were tested in each group, and the average result was taken.

[0124] II. Axial thermal conductivity A sample was cut along the axial direction of the protective tube. The axial thermal diffusivity was determined by referring to the test methods for thermal conductivity and thermal diffusivity of plastics. The axial thermal conductivity was calculated based on the sample density and specific heat capacity.

[0125] The thermal conductivity of plastics can be tested in accordance with the current GB / T 42919.4-2023 or the applicable transient planar heat source method; the radial thermal conductivity of the intact tube wall is further characterized by the above-mentioned steady-state method for cylinders.

[0126] III. Simulated Cable Operating Temperature Rise A 1m long protective pipe was horizontally buried in a test chamber with dimensions of 1.2m×1.0m×1.0m. The test chamber was filled with standard sand of the same batch, with a moisture content controlled at 5.0%±0.5% and an initial temperature of 25℃.

[0127] A cylindrical electric heating element with an outer diameter similar to that of the actual cable is installed inside the protective tube. An air gap is maintained between the heating element and the protective tube. The heating power is 65W / m.

[0128] After continuous heating for 8 hours, the temperature at the center of the heated outer surface was recorded. Three samples were tested in each group, and the average value was taken.

[0129] IV. Ring Stiffness The ring stiffness of the protective pipe was determined according to GB / T 9647-2015. The test temperature was 23℃±2℃. The ring stiffness was calculated based on the data when the pipe diameter deformation reached 3% of the nominal inner diameter. GB / T 9647-2015 is the standard for determining the ring stiffness of thermoplastic pipes.

[0130] V. Impact Resistance The impact resistance test was conducted according to the clockwise rotation method specified in GB / T 14152. The specimen was pretreated at 0℃ and impacted by a drop hammer of specified mass and height. The true impact rate (TIR) ​​was calculated.

[0131] Each group consists of 20 samples. The lower the TIR value, the better the resistance to external impact.

[0132] VI. Interfacial peel strength Cut a strip sample with a width of 15 mm along the axial direction of the protective tube, and pre-fabricate an initial peeling opening with a length of 20 mm at the interface between the inner heat-conducting diffusion layer and the bearing layer or the interface between the outer heat-conducting heat dissipation layer and the bearing layer.

[0133] A 180° peel test was performed at 23°C and a speed of 50 mm / min. The peel strength of the two interfaces was recorded, and the lower value was taken as the interface peel strength of the sample.

[0134] VII. Hot and cold circulation The sample was placed in an environment of 20°C for 30 minutes, then heated to 90°C and held for 30 minutes, and then cooled to 20°C. This was one cycle, and a total of 100 cycles were performed.

[0135] After completing the cycle, observe whether interlayer cracks, bulges, and peeling occur in the sample, and measure the interfacial peel strength again.

[0136] 8. Heat aging retention rate The sample was aged in a 110℃ hot air aging chamber for 1000 hours. After being removed, it was conditioned in an environment of 23℃ and 50% relative humidity for 24 hours, and the radial thermal conductivity was measured again.

[0137] The radial thermal conductivity retention rate is calculated as the ratio of the radial thermal conductivity after aging to the radial thermal conductivity before aging.

[0138] IX. Volume Resistivity Volume resistivity was determined according to GB / T 31838.2-2019. This standard is currently used for the determination of DC volume resistivity and volume resistivity of solid insulating materials.

[0139] Table 1 Results of thermal conductivity and operating temperature rise

[0140] Table 2 Mechanical properties, interface properties, electrical insulation and aging results

[0141] Examples 1 through 3 all successfully formed radial thermal bridges penetrating the load-bearing layer, with the orientation ratio of plate-shaped hexagonal boron nitride in both the inner and outer thermal conductive layers not less than 60%. The radial thermal conductivity of the three examples was 0.72 W / (m·K), 1.08 W / (m·K), and 1.31 W / (m·K), respectively, indicating that the present invention can be implemented and achieve improved radial thermal conductivity.

[0142] Examples 4 and 5 used high-density polyethylene and polypropylene / high-density polyethylene blends as the main resins, respectively, and still achieved radial thermal conductivity of 1.02 W / (m·K) and 1.05 W / (m·K), respectively, indicating that the thermal conductivity network construction method of the present invention is not only applicable to a single polypropylene system.

[0143] Compared with Comparative Example 1, Example 2, with essentially the same inner and outer thermal conductive layer formulations and load-bearing layer structure, increased the radial thermal conductivity from 0.43 W / (m·K) to 1.08 W / (m·K), an increase of approximately 151%, by setting a radial thermal bridge. The simulated steady-state temperature of the cable heating element decreased from 72.9℃ to 56.8℃, a reduction of 16.1℃. Simultaneously, the ring stiffness only changed from 11.5 kN / m² to 11.2 kN / m², indicating that the radial thermal bridge can significantly reduce the radial thermal resistance of the load-bearing layer without significantly compromising its mechanical load-bearing capacity.

[0144] The axial thermal conductivity of Comparative Example 1 reached 1.38 W / (m·K), but the radial thermal conductivity was only 0.43 W / (m·K), and the radial / axial thermal conductivity ratio was 0.31. This indicates that relying solely on the sheet-like fillers oriented along the tangential plane in the inner and outer thermal conductive layers will produce obvious thermal anisotropy and cannot effectively solve the problem of insufficient heat dissipation in the tube wall thickness direction.

[0145] Compared to Comparative Example 2, Example 2 had the same total amount of radial thermal bridge packing, but Comparative Example 2 used sheet-like hexagonal boron nitride as the thermal bridge packing. The axial thermal conductivity of Comparative Example 2 increased to 1.58 W / (m·K), while the radial thermal conductivity was only 0.60 W / (m·K). This indicates that the sheet-like packing is still susceptible to axial stretching and local shearing after entering the radial slit channel, making it difficult to form a stable cross-thickness thermal conductive connection. Using granular insulating thermally conductive packing with an aspect ratio not greater than 3 increased the radial thermal conductivity by 80%, demonstrating a functional fit between the particle morphology and the radial thermal bridge structure.

[0146] Compared with Comparative Examples 3 and 4, Example 2, under the condition of the same total amount of radial thermal bridge filler, showed that the combination of spherical alumina and spherical boron nitride agglomerates increased the radial thermal conductivity by approximately 20% and 13.7%, respectively. This result indicates that the two types of particles are not simply added side-by-side, but rather that the difference in particle size and surface properties increases the number of particles in contact within the thermal bridge, reducing voids and interfacial thermal resistance in a single filler system.

[0147] The initial radial thermal conductivity of Example 2 and Comparative Example 5 is basically the same, indicating that whether or not an anchoring section is provided has little impact on the instantaneous thermal conductivity of the newly manufactured pipe. However, after 100 thermal cycles, the interfacial peel strength of Example 2 is still 4.5 N / mm, while that of Comparative Example 5 decreases to 0.9 N / mm, and local interlaminar cracks appear. This proves that the main technical function of the T-shaped or dovetail-shaped anchoring section is to improve the interfacial stability under thermal cycling conditions, rather than simply increasing the initial thermal conductivity.

[0148] Example 6 uses a dovetail-shaped anchoring section, and its peel strength after thermal cycling is 5.0 N / mm, which is higher than that of the T-shaped anchoring structure in Example 2. This shows that both the T-shaped and dovetail-shaped structures can achieve the anchoring effect described in the claims, with the dovetail-shaped structure providing stronger mechanical interlocking.

[0149] In Comparative Example 6, without the addition of maleic anhydride-grafted polyolefin, the radial thermal conductivity decreased from 1.08 W / (m·K) to 0.95 W / (m·K), the initial interfacial peel strength decreased from 4.8 N / mm to 1.6 N / mm, and the impact TIR increased from 5% to 20%. These results indicate that maleic anhydride-grafted polyolefin can improve filler dispersion and interfacial compatibility between different melt regions, serving as an important auxiliary characteristic for simultaneously maintaining thermal conductivity, interlayer bonding, and impact resistance.

[0150] In Comparative Example 7, the radial thermal bridge cross-sectional area accounts for only 3%. Although the ring stiffness remains high, the radial thermal conductivity is only 0.73 W / (m·K), and the simulated steady-state temperature of the heating element reaches 63.1℃, indicating that the effective area of ​​the thermal bridge is insufficient.

[0151] In Comparative Example 8, the radial thermal bridge cross-sectional area ratio was increased to 22%, and the radial thermal conductivity reached 1.35 W / (m·K), but the ring stiffness decreased to 8.7 kN / m², and the impact TIR increased to 25%. This indicates that while further increasing the proportion of thermal bridges can improve radial thermal conductivity, it will excessively fragment the continuous structure of the load-bearing layer. Therefore, limiting the radial thermal bridge cross-sectional area ratio to 5%–18% can achieve a reasonable balance between radial heat dissipation performance and mechanical properties.

[0152] In summary, the technical effect of this invention is not achieved by a single thermally conductive filler or a single layered structure, but by the synergistic effect of the following technical features: the sheet-like filler in the inner and outer thermally conductive layers is oriented along the tangential plane of the pipe wall; the radial thermally conductive bridge formed by the granular filler penetrates the load-bearing layer; the radial thermally conductive bridge connects the inner and outer thermally conductive layers; the T-shaped or dovetail-shaped anchoring section improves the interfacial stability after thermal cycling; the load-bearing layer maintains a continuous low filler or moderately reinforced polymer structure; and maleic anhydride-grafted polyolefin improves filler dispersion and multi-melt interfacial compatibility.

[0153] The above structure forms a complete heat transfer path of "heat collection and equalization on the inner surface - radial heat transfer across layers - heat expansion on the outer surface", which improves radial thermal conductivity while avoiding the loss of ring stiffness and impact performance caused by high packing of the entire pipe wall.

[0154] like Figure 1 As shown, the power cable protection pipe prepared in Example 2 consists of an inner heat-dissipating diffusion layer 1, a supporting layer 2, and an outer heat-dissipating heat dissipation layer 3, arranged sequentially from the inside out. A radial heat-conducting bridge 4 is located within the supporting layer 2 and extends continuously along the thickness direction of the pipe wall. The inner end of the radial heat-conducting bridge 4 is connected to the inner heat-dissipating diffusion layer 1, and the outer end is connected to the outer heat-dissipating heat dissipation layer 3, thereby forming a continuous material region connecting the inner heat-dissipating diffusion layer 1 and the outer heat-dissipating heat dissipation layer 3 in the radial direction of the pipe wall. The radial heat-conducting bridge 4 includes a bridging section 42 located in the supporting layer 2, and an inner end anchoring section 41 and an outer end anchoring section 43 respectively disposed at both ends of the bridging section 42. The circumferential width of the inner end anchoring section 41 and the outer end anchoring section 43 is greater than the circumferential width of the bridging section 42, and they are embedded in the inner heat-dissipating diffusion layer 1 and the outer heat-dissipating heat dissipation layer 3, respectively, forming a T-shaped fusion interface. The boundaries of each functional area in the figure are generally continuous, and no through-pores or obvious interlayer separation were observed, indicating that the multi-channel co-extrusion process used can form a radial thermal bridge structure that penetrates the load-bearing layer.

[0155] like Figure 2As shown, in Example 2, the lamellar hexagonal boron nitride 21 in the inner thermal diffusion layer is dispersed in the polyolefin matrix 22. Most of the lamellar hexagonal boron nitride 21 are elongated or lamellar in radial cross-section, and their projected long axis is generally close to the tangential direction T of the pipe wall at their location. Only a small number of particles form a large angle with the tangential direction of the pipe wall. The orientation angle of no less than 300 lamellar hexagonal boron nitride particles in different circumferential positions and multiple scanning fields was statistically analyzed. With the angle θ between the projected long axis of the particle and the tangential direction T of the pipe wall not being greater than 30° as the tangential orientation criterion, the orientation ratio of lamellar hexagonal boron nitride in the inner thermal diffusion layer of Example 2 was measured to be 75.8%. This result indicates that the shear flow in the inner annular flow channel can promote the lamellar hexagonal boron nitride to be mainly arranged along the tangential plane of the pipe wall, so that it forms a filler arrangement structure in the inner thermal diffusion layer that is conducive to the diffusion of heat along the circumference and axial direction of the pipe body.

[0156] The above are merely specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent substitutions, or modifications made based on the present invention to solve essentially the same technical problems and achieve essentially the same technical effects are all covered within the protection scope of the present invention.

Claims

1. A power cable protection pipe, comprising an inner heat-dissipating diffusion layer, a bearing layer, and an outer heat-dissipating layer arranged radially in sequence, characterized in that: The bearing layer contains multiple radial thermal bridges that extend continuously along the axial direction of the pipe and are spaced apart circumferentially. The radial thermal bridges penetrate the bearing layer along the pipe wall thickness direction, with their inner ends fused to the inner thermal diffusion layer and their outer ends fused to the outer thermal dissipation layer. Both the inner and outer thermal diffusion layers include a polyolefin matrix and sheet-like insulating thermally conductive fillers. The sheet-like insulating thermally conductive fillers are arranged along the tangential plane of the pipe wall at their respective locations. The radial thermal bridges include a polyolefin matrix and granular insulating thermally conductive fillers with an aspect ratio not greater than 3.

2. The power cable protection pipe according to claim 1, characterized in that: The number of radial heat-conducting bridges is 8 to 24, and they are evenly distributed along the circumference of the tube. The circumferential width of each radial heat-conducting bridge is 2 to 8 mm, and the area occupied by all radial heat-conducting bridges in the cross section perpendicular to the tube axis is 5% to 18% of the cross-sectional area of ​​the bearing layer.

3. The power cable protection pipe according to claim 2, characterized in that: The radial heat-conducting bridge includes a bridging section located within the load-bearing layer and anchoring sections respectively disposed at the inner and outer ends of the bridging section. The circumferential width of the anchoring section is 1.2 to 2.5 times the circumferential width of the bridging section. The inner anchoring section is embedded in the inner heat-conducting diffusion layer, and the outer anchoring section is embedded in the outer heat-conducting heat dissipation layer, so that the radial heat-conducting bridge forms a dovetail-shaped or T-shaped fusion interface with the inner heat-conducting diffusion layer and the outer heat-conducting heat dissipation layer.

4. The power cable protection pipe according to claim 1, characterized in that: The polyolefin matrix in the inner thermal diffusion layer, the support layer, the outer thermal heat dissipation layer, and the radial thermal bridge has the same main resin, which is selected from polypropylene, high-density polyethylene, and a blend of polypropylene and high-density polyethylene; the inner thermal diffusion layer, the outer thermal heat dissipation layer, and the radial thermal bridge each contain 2 to 8 parts by weight of maleic anhydride-grafted polyolefin relative to 100 parts by weight of the main resin.

5. The power cable protection pipe according to claim 4, characterized in that: The sheet-like insulating and thermally conductive filler is hexagonal boron nitride, with an average particle size D50 of 5-30 μm and an aspect ratio of 10-80. The dosage is 8-25 parts by weight per 100 parts by weight of polyolefin matrix, and at least 60% of the hexagonal boron nitride sheets have an angle of no more than 30° with the tangential plane of the tube wall at their location. The granular insulating and thermally conductive filler includes spherical alumina and spherical boron nitride agglomerates, with a mass ratio of 2:1 to 8:

1. The total dosage is 25-55 parts by weight per 100 parts by weight of polyolefin matrix.

6. The power cable protection pipe according to claim 1, characterized in that: The supporting layer comprises the following raw materials in parts by weight: 75-88 parts of impact-resistant copolymer polypropylene, 6-15 parts of polyolefin elastomer, 5-12 parts of talc, 1-5 parts of maleic anhydride-grafted polypropylene, and 0.2-0.8 parts of antioxidant; the thickness of the inner thermally conductive diffusion layer is 0.3-1.2 mm, the thickness of the outer thermally conductive heat dissipation layer is 0.5-1.5 mm, and the thickness of the supporting layer accounts for 60%-85% of the total wall thickness of the protective tube.

7. A method for preparing a power cable protection pipe as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Polyolefin matrix and sheet-like insulating thermally conductive filler are melt-mixed separately to obtain inner thermally conductive melt and outer thermally conductive melt; polyolefin matrix and granular insulating thermally conductive filler are melt-mixed to obtain thermally conductive bridge melt; the raw materials of the bearing layer are melt-mixed to obtain bearing layer melt; S2. The inner thermally conductive melt, the bearing layer melt, and the outer thermally conductive melt are respectively fed into the inner annular flow channel, the middle annular flow channel, and the outer annular flow channel of the co-extrusion die. The thermally conductive bridge melt is fed into a plurality of radially spaced slit flow channels. The outlet of the radially spaced slit flow channel passes through the middle annular flow channel radially and connects with the inner annular flow channel and the outer annular flow channel respectively. The thermally conductive bridge melt connects the inner thermally conductive melt and the outer thermally conductive melt. The co-extrusion forms a tube blank with radial thermally conductive bridges. The shear flow in the inner annular flow channel and the outer annular flow channel is used to orient the sheet-like insulating thermally conductive filler sheet along the tangential plane of the tube wall. S3. The tube blank is sequentially vacuum sizing, cooling, traction and cutting to obtain the power cable protection tube.

8. The preparation method according to claim 7, characterized in that: In step S1, 0.3% to 1.5% of silane coupling agent by mass of the filler is used to perform surface treatment on the sheet-like insulating thermally conductive filler and the granular insulating thermally conductive filler respectively; the sheet-like insulating thermally conductive filler is added to the mixing zone located in the rear half of the screw through the side feed port of the twin-screw extruder to maintain the aspect ratio of the sheet-like insulating thermally conductive filler; the granular insulating thermally conductive filler is first made into a thermally conductive bridge masterbatch by grafting maleic anhydride with polyolefin, and then diluted with polyolefin matrix to form a thermally conductive bridge melt.

9. The preparation method according to claim 7, characterized in that: In step S2, the ratio of the length of the directional section of the inner annular flow channel and the outer annular flow channel to the corresponding flow channel gap is 20 to 60; the number of radial slit flow channels is 8 to 24. The melt pressure of the thermal bridge melt entering the radial slit channel is 1.05 to 1.25 times that of the load-bearing layer melt pressure, and the co-extrusion temperature is 175 to 215°C, so that the thermal bridge melt continuously fills the radial slit channel and melts and combines with the inner and outer thermal conductive melts.

10. The preparation method according to claim 9, characterized in that: In step S3, the tube blank is vacuum sizing under a negative pressure of 0.02 to 0.06 MPa and a cooling water temperature of 15 to 35°C. The sizing tube is then heat-treated at 80 to 120°C for 15 to 45 minutes, and then cooled to room temperature at a cooling rate of 3 to 10°C / min to reduce the residual stress at the interface between the radial thermal bridge and the load-bearing layer.